2016
DOI: 10.1016/j.rmcr.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Löffler syndrome on a Louisiana pig farm

Abstract: Löffler syndrome, a fulminant eosinophilic pneumonitis associated with the larval migratory phase of human parasites, is rarely reported in the United States. A previously healthy 8-year-old male was hospitalized with tachypnea, cough, hypoxemia, and fever of one week's duration. History revealed exposure to pigs on his family's farm in southernmost Louisiana, where the patient was responsible for cleaning the farm's pigpens. His fingernails were soiled and extremely short, with the edge of the nail bed expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, zoonotic exposure is not uncommon through exposure to parasites of livestock and companion animals . Indeed, a number of relatively recent studies have identified Ascaris suum infection and associated pathology (such as Loffler syndrome) to occur (albeit at low levels) in northern European and North American pig farming areas . A more common cause of zoonotic helminth infections comes from Toxocara canis and T. cati which naturally infect dogs and cats .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, zoonotic exposure is not uncommon through exposure to parasites of livestock and companion animals . Indeed, a number of relatively recent studies have identified Ascaris suum infection and associated pathology (such as Loffler syndrome) to occur (albeit at low levels) in northern European and North American pig farming areas . A more common cause of zoonotic helminth infections comes from Toxocara canis and T. cati which naturally infect dogs and cats .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Indeed, a number of relatively recent studies have identified Ascaris suum infection and associated pathology (such as Loffler syndrome) to occur (albeit at low levels) in northern European and North American pig farming areas. [17][18][19][20] A more common cause of zoonotic helminth infections comes from Toxocara canis and T. cati which naturally infect dogs and cats. 21 According to recent studies, levels of human exposure to these parasites can vary from 6% to 87% depending on age and local environmental factors.…”
mentioning
confidence: 99%
“…However, highly endemic porcine ascariasis is present in some farmed pigs in the United States ( 7 ). Sporadic reports have been documented of autochthonous ascariasis cases and case clusters in northeastern states ( 8 ), and Ascaris lumbricoides roundworm–mediated Löffler syndrome (eosinophilic pneumonitis) has been reported in Louisiana over the past decade ( 9 ). Those autochthonous ascariasis cases represented spillover infections to humans from pigs.…”
mentioning
confidence: 99%
“…Heavy infections may also cause malabsorption and stunting with consequent vitamin deficiencies, growth retardation, altered immunity, and impaired cognition ( 7 , 10 ). A larva migrans syndrome may be observed, caused by immune-mediated responses to the visceral migration of A. lumbricoides worm larvae through the lungs and appearing as Löffler syndrome ( 9 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation